Preferences among young people between public and private sexual and reproductive health services - Notara, Venetia; Zoitaki, Theodora; Sakellari, Evanthia; Lagiou, Areti (International Journal of Population Data Science, 2022)
Background Sexual and reproductive health services aim at the promotion of sexual health and elimination of the risk of sexually transmitted infections (STI’s). Therefore, they constitute an important framework for the improvement of young people's quality of life. The aim of this study was to investigate the main reasons that young people visit these services and furthermore what drives the choice between public and private sector. Methods The study included participants aged 18-20 years, living in the capital city of Athens, Greece. The questionnaire was developed for the purposes of the current study, including questions about the reasons for visiting sexual and reproductive health services, preferences between public and private sector. Findings From 162 participants who visited sexual and reproductive health services, the main reason was for a Pap test (Pap smear) followed by STI/HIV testing, vaccination for HPV and other gynecological tests (i.e. ultrasounds). The majority of the participants, though not significant, preferred the private compared to public sector (n=127 vs n=35, respectively). The main reasons for choosing the private sector was accessibility and flexibility of appointments (p=0.02) and privacy (p=0.008). Even though, most of the participants (61.1%) who visited the private sector were informed about the existence of public sexual and reproductive health services. Conclusions Convenience and privacy seemed to be the most important reasons for visiting the private sector. Efforts should be made for public sexual and reproductive health services in order to be more accessible and flexible to young people. These efforts can be supported by community engagement initiatives.